Legal Democratization of the Existence of Indigenous Peoples - Noya, Ekberth Vallen (Faculty of Law, Universitas Pattimura, 2023)
This article describes the position of indigenous peoples who are starting to be marginalized due to the democratization process of existing laws. This article aims to show how far the process of legal democratization has progressed so that indigenous peoples are often marginalized while the law should uphold human rights. The research method used is the normative research method, and the research approaches used are the statute approach, the conceptual approach, and the analytical approach, so that they can help examine and find good research results. The democratic method begins with the freedom of the right to vote, which allows every citizen to participate in making political decisions. Each participant has equal rights in determining their own choices and also has the opportunity to be elected. The principle of a majority vote is essential to reaching decisions in the concept of democracy.